PRODUKTIVITAS DAN RENDEMEN INDUSTRI KERAJINAN BIJI KOKKA DI DESA ANTASAN SENOR ILIR KECAMATAN MARTAPURA TIMUR KALIMANTAN SELATAN - Chairil Nurifani; Kurdiansyah Kurdiansyah; Siti Hamidah (Jurnal Sylva Scienteae, 2022)
Non-timber forest product is the use of plants other than wood or timber in forest or non-forest environment. Generally non-timber forest products are utilized for personal needs, sold away or as a material for handicrafts. One example of a non-timber forest product that is used a material for handicrafts are kokka seeds. Popular handicrafts made from kokka seeds are bracelets, prayer beads, and rings. Looking at the available potentials, kokka seeds craftsmen in Antasan Senor Ilir village are guiding the craftsmen so that the product that are produced are of good quality and compete in local or foreign market. But until now, the data that explains the level of productivity and yield of kokka crafts is non-existent. Based on that fact, the writer is interested in researching the productivity and yield of kokka crafts in antasan senor ilir village, east martapura district. The method used to calculate productivity is the output of work results which consists of kokka seed products and the total time, which is the time needed to produce one complete product. Observation of the yield of kokka seed crafts uses a scale to find out the mass of materials before it is processed and the mass of materials ofter it is processed into a product. Based on, research results, respondent with the highest productivity kosasi with 233,92 gr/ hours and 629 kg/ year. Respondent with the lowest productifity overall is Nurul beuti with 389 kg/ year. Factors that effects productivity is the length or working experience, motivation, age, and education. The yield of kokka seed ranges from 75,00% to 88,00%, with the average of the whole kokka seed yield at 82,31%. Respondent with 1 kg of materials produce an output of 0,88 kg, so that the yield of kokka seeds of 88,00% becomes the highest yield. The lowest kokka seed yield sits at 75,00%, with 1,04 kg of material and an output reaching only 0,78.Hasil hutan non kayu adalah pemanfaatkan jenis tumbuhan di kawasan hutan maupun diluar kawasan hutan selain kayu. Umumnya hasil hutan bukan kayu digunakan untuk kebutuhan atau kepentingan sendiri, dijual, serta untuk bahan baku kerajinan. Salah satu hasil hutan bukan kayu yang digunakan sebagai bahan kerajinan yaitu biji kokka. Kerajinan biji kokka yang populer dan banyak diminati konsumen berupa gelang, tasbih, dan cincin. Melihat potensi yang ada pengrajin biji kokka di Desa Antasan Senor Ilir terus membina para pengrajin sehingga produk yang akan dihasilkan memiliki mutu yang baik dan mampu bersaing di pasaran lokal maupun diluar. Namun sampai saat ini untuk data yang menjelaskan tinggi rendahnya angka produktivitas serta rendemen pembuatan kerajinan biji kokka masih tidak ada. Dengan tidak adanya data tersebut maka penulis berminat untuk meneliti produktivitas dan rendemen kerajinan kokka di desa Antasan Selor Ilir Kecamatan Martapura Timur. Metode yang digunakan untuk menghitung tingkat produktivitas yaitu, output adalah hasil kerja berupa sebuah produk dari kerajinan biji kokka dan waktu total adalah waktu yang yang dibutuhkan untuk membuat satu buah produk. pengamatan rendemen kerajinan biji kokka menggunakan timbangan untuk mengetahui berat bahan baku, sebelum diolah dan setelah menjadi produk. Berdasarkan hasil penelitian responden dengan produktivitas tertinggi yaitu Kosasi 233,92 gr/jam dan 629 kg/tahun. Responden yang memiliki produktivitas terendah secara keseluruhan yaitu Nurul Beuti dengan produktivitas hanya 389 Kg/tahun. Faktor yang mempengaruhi produktivitas yaitu lamanya bekerja, motivasi, usia, dan pendidikan. Rendemen biji kokka berkisar dari 75,00% sampai dengan 88,00% dengan rerata keseluruhan rendemen kerajinan kokka 82,31%. Responden dengan bahan baku 1,00 kg menghasilkan output 0,88 kg sehingga rendemen biji kokka menjadi 88,00% menjadi rendemen tertinggi. Rendemen biji kokka terendah yaitu 75,00% dengan bahan baku 1,04 kg dan output yang hanya mencapai 0,78 kg.